Prorocentrum pervagatum sp. nov. (Prorocentrales, Dinophyceae): A new, small, planktonic species with a global distribution. Issue 1 (20th October 2022) - Tillmann, Urban; Wietkamp, Stephan; Gottschling, Marc; Hoppenrath, Mona
SUMMARY: Prorocentrum comprises a unique group of dinophytes with several apomorphic traits, such as an apical insertion of flagella and the presence of two major, large thecal plates. Species delimitation is challenging, especially for morphologically very similar, small planktonic species. Contemporary analyses, including SEM studies and molecular phylogenetics of type material, are not available for many described species. Based on six strains isolated from Antarctic, subarctic and North Atlantic waters, Prorocentrum pervagatum sp. nov. is described. Prorocentrum pervagatum was small (12–16 μm long and deep), oval to round in outline, and moderately compressed. One small, pyrenoid‐like structure was faintly visible in some cells. Rod‐like, long trichocysts were present. Cells had one distinct apical spine (1.1–1.7 μm in length) visible in light microscopy. The plate surface appeared smooth in light microscopy with few pores located close to the plate margin visible in empty thecae. Electron microscopy revealed plates to be densely covered by small projections and two size classes of thecal pores. Cells had a row of mostly four large pores in apical‐ventral position on the right thecal plate. The periflagellar area consisted of eight small platelets. The apical spine was formed by platelet six. In molecular phylogenetics, P. pervagatum was part of a species group generally exhibiting small size and spiny thecal ornamentation, together with Prorocentrum cordatum and Prorocentrum obtusidens . The new species is distinct in DNA trees and differs from the protologues of other small species of Prorocentrum by the unique combination of size, shape (i.e. only moderately compressed or round), presence of a distinct apical spine, and position of thecal pores (i.e. located at the plate margins only). Its clear description and illustration may stimulate similar work of other small species of Prorocentrum, particularly including the re‐investigation of taxa with historical names collected at the corresponding type localities.